Direct visualization of DNA baton pass between replication factors bound to PCNA. Issue 1 (December 2018) - Mayanagi, Kouta; Ishino, Sonoko; Shirai, Tsuyoshi; Oyama, Takuji; Kiyonari, Shinichi; Kohda, Daisuke; Morikawa, Kosuke; Ishino, Yoshizumi
Abstract In Eukarya and Archaea, the lagging strand synthesis is accomplished mainly by three key factors, DNA polymerase (Pol), flap endonuclease (FEN), and DNA ligase (Lig), in the DNA replication process. These three factors form important complexes with proliferating cell nuclear antigen (PCNA), thereby constructing a platform that enable each protein factor to act successively and smoothly on DNA. The structures of the Pol-PCNA-DNA and Lig-PCNA-DNA complexes alone have been visualized by single particle analysis. However, the FEN-PCNA-DNA complex structure remains unknown. In this report, we for the first time present this tertiary structure determined by single particle analysis. We also successfully visualized the structure of the FEN-Lig-PCNA-DNA complex, corresponding to a putative intermediate state between the removal of the DNA flap by FEN and the sealing of the nicked DNA by Lig. This structural study presents the direct visualization of the handing-over action, which proceeds between different replication factors on a single PCNA clamp bound to DNA. We detected a drastic conversion of the DNA from a bent form to a straight form, in addition to the dynamic motions of replication factors in the switching process.